2020
DOI: 10.1128/msphere.00756-20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Description of a High-Copy IncQ1 KPC-2 Plasmid Harbored by the International ST15 Klebsiella pneumoniae Clone

Abstract: This study provides the genomic characterization and clinical description of bloodstream infections (BSI) cases due to ST15 KPC-2 producer Klebsiella pneumoniae. Six KPC-K. pneumoniae isolates were recovered in 2015 in a tertiary Brazilian hospital and were analyzed by whole-genome sequencing (WGS) (Illumina MiSeq short reads). Of these, two isolates were further analyzed by Nanopore MinION sequencing, allowing complete chromosome and plasmid circularization (hybrid assembly), using Unicycler software. The cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…All ST15 strains were susceptible to amikacin in our study, while the resistant rates to amikacin were 100% reported in Vietnam 11 and Shanghai, China. 16 The diversity of plasmid types acquired by ST15 clones in the different study locations, such as bla KPC-2 -bearing IncQ1 plasmid in Brazil, 17 bla KPC-2 -bearing IncFII plasmid in Bulgaria, 10 bla KPC-3 -bearing IncF plasmid in Portugal 12 and bla OXA-232 -bearing ColKP3 plasmid in China, 16 suggests this clone has a high capacity for horizontal acquisition of resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All ST15 strains were susceptible to amikacin in our study, while the resistant rates to amikacin were 100% reported in Vietnam 11 and Shanghai, China. 16 The diversity of plasmid types acquired by ST15 clones in the different study locations, such as bla KPC-2 -bearing IncQ1 plasmid in Brazil, 17 bla KPC-2 -bearing IncFII plasmid in Bulgaria, 10 bla KPC-3 -bearing IncF plasmid in Portugal 12 and bla OXA-232 -bearing ColKP3 plasmid in China, 16 suggests this clone has a high capacity for horizontal acquisition of resistance.…”
Section: Discussionmentioning
confidence: 99%
“… 10–16 K. pneumoniae ST15 strains in different regions are variable in terms of antimicrobial resistance patterns and resistance genes, which is likely related to the differences in plasmid types carrying antimicrobial resistance genes. 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IncQ1 type plasmids are efficient antimicrobial resistance determinants among Gram-negative bacteria (35). The truncated IncQ1 replicon in the plasmid pKP32558-2-mcr8 was also observed in the other two plasmids, pMCR8_020135 and pMCR8_095845, indicating that these three plasmids may share a common ancestor.…”
Section: Discussionmentioning
confidence: 98%
“…CC-BY-NC-ND 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is The copyright holder for this preprint this version posted July 23, 2021. ; https://doi.org/10.1101/2021.07.21.453302 doi: bioRxiv preprint IncQ1 type plasmids are efficient antimicrobial resistance determinants among Gram-negative bacteria (35). The truncated IncQ1 replicon in the plasmid pKP32558-2-mcr8 was also observed in the other two plasmids, pMCR8_020135 and pMCR8_095845, indicating that these three plasmids may share a common ancestor.…”
Section: Discussionmentioning
confidence: 99%